2016
DOI: 10.5392/jkca.2016.16.05.623
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Online Social Relationship on Depression among Older Adults in South Korea

Abstract: This study examined the importance of social capital in facilitating older adults' learning and adaptation of information technology as well as alleviating depressive symptoms.At two senior community centers in South Korea, 144 adults aged 60 and older were recruited to participate in 12 week-long technology classes to learn computers, smart phone, and internet skills. At the baseline interviews were conducted to assess their health status, depression, and online social relationships. Online and offline social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
1
0
4
Order By: Relevance
“…Smartphones can be an effective method to improve and maintain cognitive function and decrease depression in older adults aged 65 years or older [29]. Additionally, it has been shown that information technology and online social interaction can be used to influence geriatric depression directly [30]. This study suggests that online networking as a form of social support can be utilized as an intervention for geriatric depression.…”
Section: Discussionmentioning
confidence: 97%
“…Smartphones can be an effective method to improve and maintain cognitive function and decrease depression in older adults aged 65 years or older [29]. Additionally, it has been shown that information technology and online social interaction can be used to influence geriatric depression directly [30]. This study suggests that online networking as a form of social support can be utilized as an intervention for geriatric depression.…”
Section: Discussionmentioning
confidence: 97%
“…또 다른 가능성으로는, 온라인 상에서 새로운 관계를 구축하고 인간관계를 확장함으로써 사회적 지지 기반을 넓혀갈 가능성도 있다. 아직 우리나라 노인들이 온라인 상에서 모르는 사람들을 만나 새로운 관계를 맺는 행동에 대한 연구가 많지 않지만, Yoon 등[ 17 ]의 연구 결과를 참고해볼 만하다. Yoon 등[ 17 ]은 사회적 네트워크의 두 종류인 결속형(bonding)과 가교형(bridging) 사회자본의 개념을 이용하여 노인의 온라인 사회관계를 측정하였다.…”
Section: Discussionunclassified
“…아직 우리나라 노인들이 온라인 상에서 모르는 사람들을 만나 새로운 관계를 맺는 행동에 대한 연구가 많지 않지만, Yoon 등[ 17 ]의 연구 결과를 참고해볼 만하다. Yoon 등[ 17 ]은 사회적 네트워크의 두 종류인 결속형(bonding)과 가교형(bridging) 사회자본의 개념을 이용하여 노인의 온라인 사회관계를 측정하였다. 결속형은 이미 알고 있는 사람들과의 사회적 네트워크로 가족, 친구 등 기존의 관계가 더욱 강화되는 사회자본이다.…”
Section: Discussionunclassified
See 2 more Smart Citations